Emotional Intelligence - The Notion and The Dilemma of Islamization From Qurʾānic Perspective: An Analytical Study - Bey Zekkoub, Abdelali (Penerbit Hellow Pustaka, 2024)
. Modern studies have shown significant interest in the field of emotional intelligence, predominantly from a Western perspective, However, this concept has also received considerable attention in Qurʾānic guidance, which emphasize regulating emotions within oneself and others, Problem solving and effectively utilizing emotional intelligence to navigate one's environment. Hence, this research aims to extract a comprehensive definition of emotional intelligence and explore the dilemma of its Islamization, aligning with the comprehensive Qurʾānic perspective on life. This study employs the inductive approach to trace the concept of emotional intelligence among scholars in the West and the East, and then the analytical approach to analyse the problem of Islamizing emotional intelligence according to the Qur’anic vision. The study has yielded the following conclusions: (1) Developing a new definition of emotional intelligence: ‘the positive and effective feeling in this life towards the Creator, the soul, the others, the earth and the universe’; (2) Identifying shared elements between the Western and Islamic views of emotional intelligence in three domains: (a) Understanding and managing one's own emotions, (b) Understanding and coping with emotions of others and (c) adapting to new challenges and conditions in life; (3) Proposing two new domains of emotional intelligence based on Qurʾānic principles: (a) managing positive relationships with the Creator, and (b) managing positive interactions with divine laws. Furthermore, these findings highlight the synthesis between Western psychological perspectives and Islamic teachings on emotional intelligence, offering a comprehensive understanding rooted in the Qurʾānic worldview